'Mapping' Knowledge Dissemination - Nynke Bos; Lisa Vandeberg; Anke Oerlemans; Marlies Hulscher; W. Gudrun Reijnierse (European Journal of Health Communication (EJHC))
Metaphors are commonly used in communication about complex health issues and interventions, such as immunotherapy. This study maps the use of metaphors in communication about immunotherapy and explores differences and similarities in scientific and newspaper articles, with the aim to reveal the conceptualisation of immunotherapy among academic peers and to a broader public. We compiled two datasets of scientific (N = 1,425) and newspaper (N = 2,650) articles about immunotherapy. We identified signalled metaphors in text fragments about immunotherapy, determined their source domains, and categorized which aspects of immunotherapy they described. We identified 510 text fragments with a signalled metaphor describing 10 different aspects of immunotherapy, representing 210 different metaphorical words from 23 metaphorical source domains. The two datasets largely described similar aspects of immunotherapy, such as workings of immunotherapy and role or function of immunotherapy. They referred to similar metaphorical source domains, such as war and journey, but their distribution showed different patterns. Furthermore, different metaphorical words were used in the two datasets, with the newspaper articles showing greater diversity. This study shows how immunotherapy is conceptualised and communicated, demonstrates metaphor analysis as a method to gain insight in health issues, and suggests future research with implications for practice.